Experimental Study on Cellular Lightweight Concrete (CLC) Bricks Using Gunung Sugih Sand and Foam Agent - Ayatullah Farkhi; Ronny Hasudungan Purba; Titi Ariyanti (Poltanesa, 2026)
The development of construction technology drives the need for lighter, more efficient, and environmentally friendly building materials. One of the developing innovations is the use of Cellular Lightweight Concrete (CLC) lightweight bricks that utilize foam agents as air cavity formers in the concrete mixture. This study aims to analyze the effect of the use of Gunung Sugih sand and variations in foam agents on the characteristics of Cellular Lightweight Concrete (CLC) lightweight bricks, especially in terms of volume weight and compressive strength. The study used an experimental method with a cube-shaped test object measuring 15 cm × 15 cm × 15 cm so that the cement requirement was 26 kg, Gunung Sugih sand 48.3 kg, water 8.8 liters, with variations in foam agents of 0.4 lt/m3, 0.6 lt/m3, 0.8 lt/m3, and 1 lt/m3. Material testing includes fine aggregate specific gravity, absorption, volume weight, mud content, and sieve analysis. Compressive strength testing was carried out at the age of 28 days using a Compression Testing Machine. The results of the study showed that the addition of foam agent had an effect on reducing the volume weight and compressive strength of CLC lightweight bricks. The volume weight and compressive strength of Cellular Lightweight Concrete (CLC) lightweight bricks for foam agent variations of 0.4 lt/m³, 0.6 lt/m³, 0.8 lt/m³, and 1 lt/m³ have met the requirements as lightweight bricks that are able to float. The compressive strength value decreases with increasing foam agent content, with values of 36.50 kg/cm² (3.58 Mpa), 27.08 kg/cm² (2.66 Mpa), 22.50 kg/cm² (2.21 Mpa), and 13.84 kg/cm² (1.36 Mpa), respectively. The optimal mixture composition is obtained at a foam agent variation of 0.4 lt/m³ because it provides the best balance between compressive strength and volume weight, so it can be recommended as the most effective composition in the Cellular Lightweight Concrete (CLC) lightweight brick mixture.